Geometric and design parameters of fins employed for enhancing thermal energy storage systems: a review. (February 2018) - Abdulateef, Ammar M.; Mat, Sohif; Abdulateef, Jasim; Sopian, Kamaruzzaman; Al-Abidi, Abduljalil A.
Abstract: The continuous increase in the level of green-house gas emissions and the depletion of fossil ‎fuels are identified, as the major driving forces behind efforts to effectively utilize different sources of renewable energy. Solar energy ‎considered one of the most prospective sources of this energy. This review paper mainly focuses on the majority of heat-transfer enhancement techniques between the phase-change material (PCM) and the heat-transfer fluid (HTF) based on the application of fins embedded in the PCM. This study ‎also investigated the geometrical dimensions, dimensionless numbers, and fin location through numerical ‎and experimental works conducted to assess the influences of these parameters on the thermal performance of PCM-latent heat thermal energy storage (LHTES) containers. The best enhancement is ‎achieved using the longitudinal finned configurations because of its easy design and fabrication, especially along circumference of the cylindrical PCM containers. The circular-finned tube was also more effective than the pinned-tube for different shell and tube. PCMs based on heat sinks with internal pin fins were widely used for the thermal ‎management of various pieces of electronic products. The heat enhancement factor was effectively dependent on increasing the numbers and dimensions ‎of these fins. Further researches still require to explore the ‎possible geometrical designs of fins and their key findings, which have more effect on the thermal performance of the ‎finned-LHTES system.